The Effectiveness of Demonstrating Handwashing Practices on Hand Hygiene Behavior Among School-Age Children in Tango Molas Village - Astuti, Mennasinta Dewi; Iwa, Kornelia Romana; Danal, Paskaliana Hilpriska (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Demonstrating handwashing with soap under running water can reduce or even eliminate pathogens that cause infectious diseases. Hand hygiene refers to the act of cleaning hands using soap and rinsing under running water or using alcohol-based hand sanitizers. This study aimed to determine the effectiveness of handwashing demonstrations on hand hygiene behavior among school-age children in Tango Molas Village. The study used a quantitative method with a quasi-experimental design, specifically a control group pre-test–post-test approach. The control group consisted of students from SDI Rewung, while the intervention group consisted of students from SDI Kengko. The results of the Wilcoxon test on hand hygiene behavior in both groups (pre- and post-test) showed that the p-value in the experimental group was 0.001, indicating a statistically significant improvement in hand hygiene behavior among school-age children in Tango Molas Village.